Do People Explicitly Make a Frame Choice Based on the Reference Point? - Honda, Hidehito; Shirasuna, Masaru; Matsuka, Toshihiko; Ueda, Kazuhiro (Frontiers in Psychology, 2018)
Previous studies have shown that when choosing one of two logically equivalent frames (e.g., “half full” or “half empty”), people tend to choose based on a reference point. For example, when the amount of water in a glass with 500ml capacity was originally 0ml (or 500ml), and then increased (or decreased) to 250ml, people tend to express the amount of water in the glass as “half full” (or “half empty”). In the present study, we examined whether participants explicitly made a frame choice based on the reference point. We conducted four behavioral experiments relating to frame choice tasks. Specifically, participants were presented with a story-based or prime-based reference point and then made a frame choice. Furthermore, participants provided their reasons for the choice. Our findings on frame choices and their reasons can be summarized as follows. First, when participants were presented with a story-based reference point, some of them reported that they made frame choices based on the reference point. Second, when a reference point was presented as a prime, participants’ frame choices were affected by this reference point. However, almost no participants reported that they made frame choices based on the reference point. These results indicate that the effect of reference points on frame choices is robust and that people do not always explicitly make frame choices based on the reference point.